Glacial Geology and Geomorphology of Terra Nova Bay (Antarctica). - BARONI, CARLO; OROMBELLI G. (1987)
During the two first Italian Antarctic Expeditions (1985/86 and 1986/87) glacial-geological and geomorphological research has been carried out in the area of Terra Nova Bay. In particular the Cenozoic glacial sediments, the Holocene raised beaches and the Holocene glacier fluctuations have been investigated. Three main glacial drifts have been recognized. The youngest drift consists of a massive matrix-supported diamict extending up to about 350 m a.s.l. on the Northern Foothills, where it contains fragments of Pelecypods and Serpulids; it was deposited by a grounded ice-shelf during the last glaciation. In the interior mountains the upper limit of the drift rises up to about 1000 m a.s.l. The young glacial drift is characterized by frequent ice-cored topography, initial weathering stages, slightly stained granitic boulders without cavernous weathering, exept in the coastal belt. The older drift, very thin and discontinuous, occurs above the previous one, up to about 600 m on the Northern Foothills, and it is characterized by red stained granitic boulders affected by cavernous weathering. A third, oldest drift occurs up to 800 m a.s.l., composed of large and scattered boulders, strongly oxidized and affected by cavernous weathering, locally resting on a strongly developed red paleosol. At higher elevations up to about 1000 m round topped glacialy abraded reliefs, devoid of any glacial cover, can be observed and represent evidence of a still older glacial stage. Holocene beaches raised up to 30 m are well known at Terra Nova Bay (Inexpressible Island and Gerlache Inlet). In addition to the ones described by previous authors, other emerged beaches have been found in several localities on the coast of the Northern Foothills, near Evans Cove and at Edmonson Point. It is possible to distinguish two groups of emerged beaches: the first one consists of the beaches at Inexpressible Island and the Northern Foothills, ranging in altitude up to about 30 m a.s.l.; the second group, not higher than 7 m, is present at the ...